2015-11-03 09:10:39
if f (x) =15x-7 then f^-1(x)=
2015-11-03 10:14:51

Hi! So, we need to find the inverse of the function f(x) = 15x - 7. To start, we must turn the f(x) into a y. y = 15x - 7. Now, we swap all the x variables for the y variables, and swap all the y variables for the x variables! x = 15y - 7. Now, we simply must work on isolating y. Assuming you know how to isolate a variable, we must do the steps below - x = 15y - 7. Add 7 on both sides. x + 7 = 15y - 7 + 7. We cannot add x and 7, as they are not like terms. So, they will remain like that, while the 7 on the right side of the equation is eliminated. x + 7 = 15y. Now we are going to divide both sides by 15, thus leaving y by itself. [latex] frac{x + 7}{15} [/latex] = 15y / 15. Since we cannot divide the left side of the equation by 15, it will remain as such. With the y variable completely isolated, our final inverse function will be: [latex] f^{1}(x)[/latex] = [latex] frac{x + 7}{15} [/latex]. Hopefully, this helps! =)